Non-CG methylation patterns shape the epigenetic landscape in Arabidopsis - Stroud, Hume; Do, Truman; Du, Jiamu; Zhong, Xuehua; Feng, Suhua; Johnson, Lianna; Patel, Dinshaw J; Jacobsen, Steven E (Nature structural & molecular biology, 2014)
Non-CG methylation is abundant in plants, but its functions are poorly understood. A new study has uncovered the contributions of each non-CG methyltransferase, including the poorly characterized methyltransferase CMT2, to DNA methylation patterning and gene silencing. The results suggest that non-CG methyltransferases participate in self-reinforcing loop mechanisms with histone H3 K9 methylation and small RNAs to control gene silencing throughout the Arabidopsis genome. DNA methylation occurs in CG and non-CG sequence contexts. Non-CG methylation is abundant in plants and is mediated by CHROMOMETHYLASE (CMT) and DOMAINS REARRANGED METHYLTRANSFERASE (DRM) proteins; however, its roles remain poorly understood. Here we characterize the roles of non-CG methylation in Arabidopsis thaliana . We show that a poorly characterized methyltransferase, CMT2, is a functional methyltransferase in vitro and in vivo . CMT2 preferentially binds histone H3 Lys9 (H3K9) dimethylation and methylates non-CG cytosines that are regulated by H3K9 methylation. We revealed the contributions and redundancies between each non-CG methyltransferase in DNA methylation patterning and in regulating transcription. We also demonstrate extensive dependencies of small-RNA accumulation and H3K9 methylation patterning on non-CG methylation, suggesting self-reinforcing mechanisms between these epigenetic factors. The results suggest that non-CG methylation patterns are critical in shaping the landscapes of histone modification and small noncoding RNA.